The Portrayal of the Father-Figure in Barack Obama’s Dreams from My Father - Odanga, Denish; Odhiambo, Elizabeth; Mosoti, Edwin (The International Journal Of Humanities & Social Studies, 2017)
This article examines the portrayal of the absent father-figure in African American autobiographies. In particular, the article discusses how Obama relies on memories and reflections to prop the image of his absent father in his autobiography, Dreams from my father. The article adopted an analytical research design. Content analysis was used to generate data. The data was then coded and analyzed according to the modes of characterization. Tenets of postcolonial and psychoanalytic theories aided in reading, analysis, and interpretation of the text. Findings reveal that through dreams and reflections, Obama constructs a father who is absent from his family against his wish. Despite the severe racial discrimination, Obama Senior struggles to create a united race. Knowledge and power are divulged as the ways through which racial discrimination is based. As a result, Obama resorts to fantasies and dreams to construct a wise prince for a father.
Keywords: Absent father-figure; Memories; Dreams; Reflections; African American autobiography